2019
DOI: 10.1016/j.dadm.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Aβ and tau structure‐based biomarkers for a blood‐ and CSF‐based two‐step recruitment strategy to identify patients with dementia due to Alzheimer's disease

Abstract: Introduction Alzheimer's disease (AD) diagnosis requires invasive CSF analysis or expensive brain imaging. Therefore, a minimal‐invasive reliable and cost‐effective blood test is requested to power large clinical AD trials at reduced screening failure. Methods We applied an immuno‐infrared sensor to measure the amyloid‐β (Aβ) and tau secondary structure distribution in plasma and CSF as structure‐based biomarkers for AD (61 disease controls, 39 AD cases). Results Within a first diagnostic screening step, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 24 publications
0
46
1
1
Order By: Relevance
“…A substantial proportion of patients with MCI or dementia with potential AD etiology appears to be misdiagnosed once followed up with amyloid PET [17], and plasma biomarkers could be evaluated as follow-up diagnostic tools. For A␤ in particular, different methods for measuring plasma concentration of the protein should be compared with one another and with a recently developed structure-based approach that measures misfolded A␤ [61]. The goal should be to standardize analysis methods across labs.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion of patients with MCI or dementia with potential AD etiology appears to be misdiagnosed once followed up with amyloid PET [17], and plasma biomarkers could be evaluated as follow-up diagnostic tools. For A␤ in particular, different methods for measuring plasma concentration of the protein should be compared with one another and with a recently developed structure-based approach that measures misfolded A␤ [61]. The goal should be to standardize analysis methods across labs.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers measured were ratios of A␤PP 669-711 /A␤ 42 and A␤ 40 /A␤ 42 and their composites, confirming that plasma A␤ might reflect brain amyloid deposition. Another group has shown that the secondary structure distribution of A␤ in blood plasma, measured by an immuno-infrared sensor, is an excellent biomarker for AD, reflecting the A␤ burden in the brain [59]. The performance of Elecsys (Roche Diagnostics, Basel, Switzerland) immunoassays to measure plasma A␤ 42 and A␤ 40 has also recently been shown to predict A␤ status in all stages of AD and their accuracy can be increased by analyzing APOE genotype [60].…”
Section: Plasma Assays As Screening Tests For Admentioning
confidence: 99%
“…It is an antibody-based method to extract all the Aβ peptides from blood samples, allowing the identification of β-sheet enriched conformations [79]. Compared to established ELISA-based tests, it does not measure the absolute biomarker concentration but the relative frequency shift in the infrared, reducing the influence of concentration fluctuations caused by biological variances [80]. Unique features of this assay are the absence of labels (enzymes, fluorescent or radioactive molecules) with potentially confounding effects, being the analytes detected based on their intrinsic physical properties, a simple and low-cost procedure and the low sample volume needed.…”
Section: Immuno-infrared Sensormentioning
confidence: 99%
“…Unique features of this assay are the absence of labels (enzymes, fluorescent or radioactive molecules) with potentially confounding effects, being the analytes detected based on their intrinsic physical properties, a simple and low-cost procedure and the low sample volume needed. It is able to identify the initial Aβ misfolding, occurring several years before clinical manifestation of AD [80].…”
Section: Immuno-infrared Sensormentioning
confidence: 99%